2003
DOI: 10.1525/maq.2003.17.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Invoking Vali: Painful Technologies of Modern Birth in South India

Abstract: As reproduction becomes increasingly biomedicalized throughout the globe, reproductive technologies are used in unique ways and imbued with different meanings. This article explores why lower–class women in south India in the 1990s were demanding to have childbirth labors induced with oxytocin drugs while rejecting anesthesia. Cultural constructions women's reproductive power are evoked and reworked in discourses of modernity that explain this preference. Discourses on relationships among gender, pain, and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 24 publications
(8 reference statements)
3
34
0
Order By: Relevance
“…12 Data from elsewhere in India too confirm the widespread misuse of oxytocin for labor acceleration during home births. [13][14][15] The application of fundal pressure is expected to increase the risk of fetal distress (hence asphyxia) and birth trauma, including intracranial hemorrhage. 16 The above-mentioned survey in Rajasthan 12 found that fundal pressure was used in 94% of home and 63% of facility deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…12 Data from elsewhere in India too confirm the widespread misuse of oxytocin for labor acceleration during home births. [13][14][15] The application of fundal pressure is expected to increase the risk of fetal distress (hence asphyxia) and birth trauma, including intracranial hemorrhage. 16 The above-mentioned survey in Rajasthan 12 found that fundal pressure was used in 94% of home and 63% of facility deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…18 Reports from elsewhere in rural Karnataka also indicate widespread intrapartum use of oxytocin, 19 whilst in Chennai, intrapartum oxytocin use was normalised as a form of ''crowd control'' in busy hospitals and ''almost routine'' for the local multi-purpose health worker during home deliveries. 20,21 A study in a poor area of Delhi reported oxytocin use in 68.9% of home deliveries, administered by private doctors in 86.8% of cases. 22 These studies are relatively small-scale and did not include appropriate control populations.…”
Section: Birthing In Uttar Pradeshmentioning
confidence: 99%
“…Intramuscular (IM) oxytocin injection during the first and second stages of labor can be dangerous because dosing cannot be adjusted in response to the strength of uterine contractions, increasing risks of uterine rupture and harm to the fetus [13]. However, IM oxytocin is reportedly common to induce and augment labor in some settings, including at home births and in health facilities; it has been claimed that IM administration is practiced for rapid delivery at the request of pregnant women or their families [11], [18], [19].…”
Section: Introductionmentioning
confidence: 99%